'URF DAN PEMBENTUKAN HUKUM ISLAM MENURUT AL-SHÂTIBÎ - Mansur Mansur (LP2M Universitas Ibrahimy, 2015)
Al-ShÃ¢thibÃ® dividing habit at two kinds of 1) al-shar'iyyah al-'awÃ¢id, that is expressed habit expressly by nash shar'Ã® 2) al-nÃ¢s bain al-jÃ¢riyyah al-'awÃ¢id, habit that happened in one society community and of shara' silent do not comment. Nonetheless, shara' also legalizeing it. In meaning, law even also follow what habit will desire. Al-ShÃ¢tibÃ® also divide evaluated habit from its its at two kinds of 1) al-'Ã¢mmah al-'awÃ¢id, habit going into effect public, do not change in all room, situation and time 2) Different habit along with friction of room, situation and time. Term this â€˜Ã¢dah by al-ShÃ¢tibÃ® given on to word 'ibÃ¢dah. Because of religious service basically is total compliance and adherence to Allah, hence 'Ã¢dah basically is more emphasizing its. But so, al-ShÃ¢tibÃ® giving exemption that habits which in it there are adherence, hence its application have to bow under nash. Implementation â€™urf al-ShÃ¢tibÃ®at practical plain in the effort forming of Islam law only going into effect at deed which do not contain adherence. In the meaning that more orienting habit at relation pattern between human being is delivered to habit going into effect. On that account, law even also will be interconnected follow change of habit.Â